Evaluating a Tahfidz Al-Qur’an Program Using the CIPP Model: Grade 12 Exam Readiness in an Indonesian Islamic Boarding School - Ahmad Akbar Fauzi; Yassir Hafidh Fitriyan; Ahmad Arfian Hafis; Mohammad Rifky; Istanto Istanto (AL-ISHLAH: Jurnal Pendidikan, 2026)
The Tahfidz Al-Qur’an program constitutes a central component of Islamic education, fostering students’ spiritual, moral, and intellectual development. However, existing studies largely assess its general effectiveness without focusing on specific student levels or employing comprehensive evaluation frameworks. This study evaluates the effectiveness of the program for 12th-grade students at YAPI Sunni Tegalgondo Islamic Boarding School, particularly in supporting preparation for final examinations.A qualitative descriptive design was employed using the CIPP (Context, Input, Process, Product) evaluation model. Data were collected through interviews and observations involving teachers, students, and school leaders. The analysis was conducted systematically across the four CIPP dimensions to ensure a holistic evaluation of program implementation.The findings indicate that the program is well-structured, with organized scheduling, competent instruction, and a strong motivational framework. These elements contribute positively to students’ academic readiness, discipline, and spiritual development. Nonetheless, challenges were identified, particularly in maintaining consistent discipline during halaqah sessions and ensuring equitable mentoring support across all participants.The results underscore the need for continuous refinement of program design, enhancement of teacher professional development, and improved policy strategies. Addressing identified challenges is essential to strengthen the effectiveness and sustainability of Qur’an-based educational programs, particularly in preparing students for both academic and spiritual success.